SMART BIOSURFACTANT NANOCARRIERS: ROS-LABILE ORAL DELIVERY SYSTEM FOR ENHANCED CELECOXIB EFFICACY IN RHEUMATOID ARTHRITIS - PRADEEPA, T.; KALIYAPERUMAL, RAJAGANAPATHY (International Journal of Applied Pharmaceutics, 2026)
Objective: The chronic autoimmune illness known as rheumatoid arthritis (RA) is typified by joint destruction, oxidative stress, and ongoing inflammation. The selective COX-2 inhibitor celecoxib is useful in the treatment of RA, although its lack of disease-specific targeting, low oral bioavailability, and poor solubility restrict its effectiveness. In order to increase absorption, offer inflammation-triggered release, and boost treatment effectiveness in RA, this study set out to create a sophorolipid-stabilized, ROS-labile nanostructured lipid carrier (NLC) system for oral celecoxib administration. Methods: Using microfluidic ethanol injection, NLCs were created with thioketal (TK)-PEG-cholesterol integrated at the interface and sophorolipid acting as a biosurfactant. Mucus penetration, epithelial transport, hemocompatibility, ROS-triggered release, and in vitro pharmacological activity in LPS-stimulated macrophages were all assessed, along with the formulation's physicochemical and interfacial characteristics. Results: Optimized NLCs displayed a size of 138±6 nm, PDI<0.2, zeta potential −21 mV, and encapsulation efficiency>90%. Under ROS exposure, drug release reached 83% at 12 h versus 21% in controls. SL-NLCs showed 3-fold higher mucus diffusivity and significantly improved Caco-2 permeability (P_app 5.7×10⁻⁶ cm/s). In vitro studies demonstrated superior cytokine suppression (TNF-α ↓68%, IL-6 ↓62%) and COX-2 downregulation. Hemolysis was<3%, indicating excellent biocompatibility. Conclusion: With improved absorption, inflammation-specific release, and strong anti-inflammatory action, ROS-labile, sophorolipid-stabilized NLCs offer a secure and efficient oral delivery system for celecoxib that may find therapeutic use in RA.